Development of Teaching Materials for Integrated Elementary School PAI Learning Design for Pancasila Student Profiles in Support of the Independent Curriculum - Siti Fatma Rizki Nurlaila (Indonesian Journal of Research and Service Studies, 2024)
This research is motivated by the lack of development of teaching materials based on Pancasila student profiles that support the independent curriculum. The story of this teaching module cannot be done immediately but must be found in the needs analysis results and trials. The aim is to develop teaching materials based on Pancasila student profiles that support an independent curriculum with good validity, reliability, and effectiveness. This type of research is development research. This development research adopts the model developed by Kemp. Development procedures include needs analysis, product design, validation, revision, and testing. Data collection techniques include tests, questionnaires, and literature studies. The research instruments are tests and questionnaires that experts validate. Data analysis techniques include testing teaching modules' validity, reliability, and effectiveness. The research results show that (1) the feasibility test results by experts, high material experts, medium media experts, and heightened language experts. Student responses were also very good to the teaching materials of the Project for Strengthening the Pancasila Student Profile-Rahmatan Lil 'Alamin Student Profile (P5-PPRA); (2) by studying the P5-PPRA integrated learning design course, students' understanding of P5-PPRA has increased significantly; and (3) the results of the effectiveness analysis show that there are differences in students' knowledge of P5-PPRA before and after the experiment. This means that developing P5-PPRA integrated learning design teaching materials effectively influences students' understanding or knowledge of P5- PPRA